If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -21 = 11x + 13 Reorder the terms: -21 + 9x = 11x + 13 Reorder the terms: -21 + 9x = 13 + 11x Solving -21 + 9x = 13 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -21 + 9x + -11x = 13 + 11x + -11x Combine like terms: 9x + -11x = -2x -21 + -2x = 13 + 11x + -11x Combine like terms: 11x + -11x = 0 -21 + -2x = 13 + 0 -21 + -2x = 13 Add '21' to each side of the equation. -21 + 21 + -2x = 13 + 21 Combine like terms: -21 + 21 = 0 0 + -2x = 13 + 21 -2x = 13 + 21 Combine like terms: 13 + 21 = 34 -2x = 34 Divide each side by '-2'. x = -17 Simplifying x = -17
| (-6x-1+4x^2)x= | | 10x-76=5x-6 | | b-6=17 | | 171-4x=23x+15 | | 35+3y-3=13y-10-4y | | (x-5)(x+4)=-x+16 | | 26k-2k+8=32k+8-8k | | 4x+64=9x+12 | | y-45/4(x-1) | | 3x-6x+x-5x= | | 4(2c-1)-2=4c+2 | | 3x^2-5ix+3=0 | | -6(10-4f)=-39(-12-8f) | | 7/6=42/x | | 199-5x=31x+15 | | 4/7=x/28 | | 4.2x-9=3(1.2x+y) | | 2x+9x=55 | | 5w-6=-36 | | x/40=5/100 | | 5+x-3=3 | | -6p+7=3(2p+-3)+-4(-10+4p) | | 15/20=x/8 | | -15-4=5-9x | | 51/5-25/6 | | e-8=21 | | 6x+9=-87x-10 | | x/2=8/4 | | 3x+31=5x-5 | | 5x-19=-7(1-x) | | -5x+8*5= | | 5/7=35/x |